0 \\ x - 16x + 4 {x}^{2} > 0 \\ - 15x + 4 {x}^{2} > 0 \\ x( - 15 + 4x) > 0 \\ x( - 15 + 4x) = 0 \\ x = 0 \: \: \: and \: \: \: - 15 + 4x = 0 \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: x = \frac{15}{4} \\ + + + (0) - - - ( \frac{15}{4} ) + + + \: \\ x \in( - \infty;0)\cup( \frac{15}{4} ;+ \infty)" alt=" \frac{x}{4} - 4x + {x}^{2} > 0 \\ x - 16x + 4 {x}^{2} > 0 \\ - 15x + 4 {x}^{2} > 0 \\ x( - 15 + 4x) > 0 \\ x( - 15 + 4x) = 0 \\ x = 0 \: \: \: and \: \: \: - 15 + 4x = 0 \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: x = \frac{15}{4} \\ + + + (0) - - - ( \frac{15}{4} ) + + + \: \\ x \in( - \infty;0)\cup( \frac{15}{4} ;+ \infty)" align="absmiddle" class="latex-formula">